Metafora dalam Lirik Lagu “Mendarah” oleh Nadin Amizah - Ayudia Helmi; Widya Utari; Adelliya Yuwanda Putri; Frinawaty Lestarina Barus; Alya Luthifah (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2021)
The use of literary techniques such as metaphor is commonly found in imaginative writing such as song lyrics. In addition, metaphors can enrich the aesthetic and atmospheric elements in a musical work. This study aims to discuss the element of metaphor in the lyrics of the song